Foreign Policy and Poverty Reduction: A Comparative Study of Ghana and Nigeria - KIA, Bariledum; OYOMBIO, Ben E.; SOMIARI, Derego (Socialscientia: Journal of Social Sciences and Humanities, 2025)
The intricacy of development in a globalised context requires the use of foreign policy instruments to tackle domestic issues, such as poverty alleviation. Poverty is a substantial obstacle for emerging nations such as Nigeria and Ghana. Recent poverty reduction efforts signify a substantial shift in the foreign policy towards socio-economic development plans and objectives. This is a significant cause of worry and thus requires additional examination. The research conducts a preliminary analysis of the foreign policy goals of both nations and their impact on poverty reduction, aiming to evaluate the degree to which economic development foreign policy has aided in mitigating poverty challenges in both countries. The study used a mixed-methods approach, integrating qualitative and quantitative techniques to validate results, using neoliberal theory as its analytical framework. The used metrics were Gross Domestic Product, Poverty Reduction Ratio, Human Development Index, and Multidimensional Index. The study’s data were sourced from declassified papers of both nations, the World Bank, the United Nations, the African Development Bank, and the National Statistical Office. Content and discourse analysis methodologies were used to scrutinise the data collected for the study. The study’s findings indicate that both nations saw variations in GDP. Nigeria: 362.81; Ghana: 76.37; poverty The headcount ratio indicates that Nigeria has 82.9 million people, whilst Ghana has 31.3%. The multidimensional index reveals that, among the 1.1 billion inhabitants globally, Nigeria has a substantial population living in poverty, whilst Ghana has a comparatively smaller proportion in similar circumstances. The study’s findings reveal that Ghana employed a broader array of foreign policy instruments, including the attraction of foreign investments, promotion of international cooperation, and establishment of partnerships, to address poverty issues in contrast to Nigeria. The research recommends that Nigeria and other African countries synchronise their foreign policy priorities with national development objectives and cultivate international partnerships for poverty alleviation.